Forensic archaeology : the application of comparative excavation methods and recording systems - Evis, Laura, (Archaeopress archaeology., 2016)
This text evaluates current archaeological excavation methods and recording systems in relation to their use in providing forensic evidence, and their ability to satisfy the admissibility tests introduced by the Law Commission, and other internationally recognised bodies.